UPAYA MENINGKATKAN KETERAMPILAN MOTORIK HALUS MELALUI KEGIATAN MENJAHIT POLA PADA ANAK USIA 4-5 TAHUN DI RA TAMOPONRENG KELURAHAN MACEGE KECAMATAN TANETE RIATTANG BARAT - Nurul Huda; Hasan Basri; A.Sri Mardiyanti Syam3 (EDUCHILD (Journal of Early Childhood Education), 2025)
This thesis discusses efforts to improve fine motor skills through pattern-sewing activities for children aged 4–5 years at RA Tamoponreng, Macege Village, Tanete Riattang Barat District. The purpose of this study is to determine the fine motor skills of early childhood through pattern-sewing activities at RA Tamoponreng, Manurunge Village, Tanete Riattang Barat District. This study uses a quantitative approach with a Pre-Experimental Design, specifically the One Group Pretest–Posttest model. The research was conducted at RA Tamoponreng, Macege Village, Tanete Riattang Barat District, with a sample of 10 children. The study employed a pedagogical approach, and the data were collected through observation and testing. The data obtained during the study were analyzed using SPSS for Windows version 22 to determine the results of descriptive statistics for the pretest and posttest, as well as the paired sample t-test. The results show that pattern-sewing activities can improve fine motor skills in Group A at RA Tamoponreng, Macege Village, Tanete Riattang Barat District. This is evidenced by the t-test results for the pretest and posttest, where the significance value (2-tailed) of 0.000 < 0.05 indicates that H0 is rejected and H1 is accepted. Therefore, it can be concluded that pattern-sewing activities significantly enhance fine motor skills in children. Keywords: Fine Motor Skills, Pattern Sewing